Doktrin Keagamaan Nahdlatul Ulama Sebagai Role Model Toleransi Umat - Sariroh, ST; Ali, Moh; Amri, Amri; Syakur, Abd (POROS ONIM: Jurnal Sosial Keagamaan, 2022)
The crisis of tolerance between religious communities in various parts of the world is increasing, including in Indonesia. So it needs to be reaffirmed, with the existence of religious community organizations such as Nahdlattul Ulama which has a high flow of tolerance between religious communities, it must be used as a mecca/role model for tolerance. This study uses the literature search method combined with the latest information on religious tolerance. The results of the study stated that inter-religious tolerance can be achieved by implementing hablum minallah hablum minannas hablum mina nas and hablum minal alam as religious teachings in community empowerment, opening up business fields, trying to maintain the nation and state together, and maintaining relationships among people. In Indonesia, it seems that there will be no difficulties if all parties are aware of the religious values being taught, especially within the Nahdlatul Ulama environment which can be taken out and become a mecca for tolerance in various matters and various fields of life.